X⁴ - 22x² - 75 = 0 Разложим на множители и решим: ( x - 5)( x + 5)( x² +3) = 0 Произведение равно 0,когда один из множителей равен 0,значит, ( x - 5)( x + 5)( x² + 3) = 0 x - 5 = 0 x = 5 x + 5 = 0 x = - 5 x² + 3 = 0 x² = - 3 - корней нет. ответ: x = 5, x = - 5
Разложим на множители и решим:
( x - 5)( x + 5)( x² +3) = 0
Произведение равно 0,когда один из множителей равен 0,значит,
( x - 5)( x + 5)( x² + 3) = 0
x - 5 = 0
x = 5
x + 5 = 0
x = - 5
x² + 3 = 0
x² = - 3 - корней нет.
ответ: x = 5, x = - 5